Characterization and genomic analysis of a bensulfuron methyl-degrading endophytic bacterium Proteus sp. CD3 isolated from barnyard grass (Echinochloa crus-galli) - Wang, Yanhui; Chen, Xianyan; Li, Honghong; Ma, Yonglin; Zeng, Dongqiang; Du, Liangwei; Jin, Decai (Frontiers in Microbiology, 2022)
Bensulfuron methyl (BSM) is a widely used sulfonylurea herbicide in agriculture. However, the large-scale BSM application causes severe environmental problems. Biodegradation is an important way to remove BSM residue. In this study, an endophytic bacterium strain CD3, newly isolated from barnyard grass (Echinochloa crus-galli), could effectively degrade BSM in mineral salt medium. The strain CD3 was identified as Proteus sp. based on the phenotypic features, physiological biochemical characteristics, and 16S rRNA gene sequence. The suitable conditions for BSM degradation by this strain were 20–40°C, pH 6–8, the initial concertation of 12.5–200 mg L−1 with 10 g L−1 glucose as additional carbon source. The endophyte was capable of degrading above 98% BSM within 7 d under the optimal degrading conditions. Furthermore, strain CD3 could also effectively degrade other sulfonylurea herbicides including nicosulfuron, halosulfuron methyl, pyrazosulfuron, and ethoxysulfuron. Extracellular enzyme played a critical role on the BSM degradation by strain CD3. Two degrading metabolites were detected and identified by using liquid chromatography–mass spectrometry (LC–MS). The biochemical degradation pathways of BSM by this endophyte were proposed. The genomic analysis of strain CD3 revealed the presence of putative hydrolase or esterase genes involved in BSM degradation, suggesting that a novel degradation enzyme for BSM was present in this BSM-degrading Proteus sp. CD3. The results of this research suggested that strain CD3 may have potential for using in the bioremediation of BSM-contaminated environment.